Nurturing An Islamic Identity Throughout Familial Conflict Among New Reverts : A Critical Review - Faisal Azni, N. L.; Md Yusoff, Y. (Universiti Sains Islam Malaysia, 2024)
In regards to the integrated fields of psychology, da'wah and the Islamic studies, little research has been conducted to examine the areas of identity sustainment and/ or psychological dissociation in the process of Islamic reversion. Admittedly, while a few studies have broached on the difficulties of reverts adapting to an Islamic lifestyle, there is a gap in understanding how their very identities are affected by the factors of Islamic reversion and psychological dissociation due to conflict. In light of the above, this paper aims to investigate the phenomenon of nurturing an Islamic identity throughout the existence of familial conflict among new reverts to Islam by critically reviewing the literature of various researches to examine three main influences in conjunction to the research phenomenon above. The first is the influence of a familial misconception of Islam on the existence of familial conflict. The second is the influence of familial conflict on a difficulty sustaining an Islamic identity, and the third is the influence of psychological dissociation on sustaining an Islamic identity. Consequently, this critical review was conducted by analyzing and discussing the findings from both locally Malaysian and international researches concerning the three specified fields mentioned above. In conclusion, this paper was written with the hopes of opening up new approaches of dialogue between the global models of religion in the human psyche and their Muslim counterparts, with the ultimate aim of inducing a dialogue which would enrich both perspectives, and advance the fields of psychology, Da'wah and the Islamic studies.